Strong intramolecular DyIII–DyIII magnetic couplings up to 15.00 cm−1 in phenoxyl-bridged dinuclear 4f complexes. (22nd January 2020) - Zhang, Wei; Xu, Shao-Min; Zhu, Zhao-Xia; Ru, Jing; Zhang, Yi-Quan; Yao, Min-Xia
Abstract : Unexpectedly, intramoleular Dy III –Dy III magnetic couplings are up to 15.00 cm −1 in the phenolate-bridged Dy2 complexes. And single-molecule magnet behavior is exhibited with effective energy of 76.18 K under zero dc field. Abstract : Three phenoxyl-bridged dinuclear lanthanide complexes [Ln2 (dbm)2 (LH2 )2 ]·H2 O (Ln = Gd for 1, Tb for 2, and Dy for 3, LH3 = (1 E, 3 E )-2-hydroxy-5-methylisophthalaldehyde dioxime, Hdbm = dibenzoylmethane) were synthesized, and structurally and magnetically characterized. In these complexes, Ln III ions are eight coordinated and lie in D 4d local symmetry. Intramolecular ferromagnetic couplings are exhibited between Ln III ions. Surprisingly, the intramolecular Dy III –Dy III magnetic couplings are up to 15.00 cm −1, which are the strongest ones of the reported Dy2 complexes by phenoxyl bridges. Complex 3 shows single-molecule magnet behavior with an effective energy of 76.18 K under zero dc field which is in accordance with the calculated value. The magnetostructural correlation of phenoxyl-bridged Dy2 complexes is analyzed.